Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18632/oncotarget.16191
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma-specific expression of P2Y11 receptor and its contribution in ATP-induced purinergic signalling and cell migration in human hepatocellular carcinoma cells

Abstract: Extracellular ATP-induced Ca2+ signalling is critical in regulating diverse physiological and disease processes. Emerging evidence suggests high concentrations of extracellular ATP in tumour tissues. In this study, we examined the P2 receptor for ATP-induced Ca2+ signalling in human hepatocellular carcinoma (HCC) cells. Fura-2-based measurements of the intracellular Ca2+ concentration ([Ca2+]i) showed that extracellular ATP induced an increase in the [Ca2+]i in human HCC Huh-7 and HepG2 cells. NF546, a P2Y11 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…Consistent with our observations, ATP has been reported to induce hepatocellular carcinoma cell migration through P2Y11 . Our results showing that ATP induces migration in deciliated cells and iCCA cells are in line with these data because hepatocellular carcinoma cells, like normal hepatocytes and CCA cells, do not express primary cilia.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our observations, ATP has been reported to induce hepatocellular carcinoma cell migration through P2Y11 . Our results showing that ATP induces migration in deciliated cells and iCCA cells are in line with these data because hepatocellular carcinoma cells, like normal hepatocytes and CCA cells, do not express primary cilia.…”
Section: Discussionsupporting
confidence: 93%
“…There is upregulation of P2Y 2 R in human hepatocellular carcinoma cells ( Tak et al, 2016 ), which mediates proliferation and migration of the cells ( Xie et al, 2014 ). Carcinoma-specific expression of P2Y 11 R make a major contribution to ATP-induced signalling that controls cell migration in human hepatocellular carcinoma cells ( Khalid et al, 2017 ). CD39 KO mice showed an increased incidence of spontaneous and induced hepatocellular carcinoma.…”
Section: Diseases Of the Livermentioning
confidence: 99%
“…First, we examined the expression level of P2Y11R in human FLS, with HepG2 cancer cells as a positive control . We found that the mRNA and protein expression of P2Y11R in synoviocytes is comparable to that of HepG2 cells (Figure a,b).…”
Section: Resultsmentioning
confidence: 88%
“…13 Treatment with NF340 has been reported to prevent ATP-induced stimulation of cell migration and Ca 2+ signaling in human hepatocellular carcinoma cells. 15 In our study of FLS in RA, we report that P2Y11R is a highly specific inducible factor that responds to cytokine stimulation and we present our evaluation of the effect of P2Y11 receptor antagonism in FLS.…”
Section: Introductionmentioning
confidence: 99%